Carbon pricing of basic materials: Incentives and risks for the value chain and consumers - Jan Stede; Stefan Pauliuk; Gilang Hardadi; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
For the European Union to realise its ambition of carbon neutrality, emissions from basic material production need to be reduced through low-carbon production processes, material efficiency and substitution, as well as enhanced recycling. Different reform options for the EU ETS are discussed that ensure a consistent carbon price incentive for all these mitigation options, while avoiding the risk of carbon leakage. This paper offers a first quantification of potential carbon leakage risks, distributional implications and additional revenues associated with different mechanisms: an import- only border carbon adjustment (BCA), a symmetric BCA, and an excise for embodied carbon emissions at a fixed benchmark level in combination with continued free allocation. We estimate the product-level carbon intensities for about 4,400 commodity groups, including basic materials, material products, and manufactured goods and compute implied price changes and cost increases relative to gross value added to assess the scale of carbon leakage risks.
Keywords: F18; C67; 330; emissions trading; border carbon adjustment (BCA); excise duty; carbon intensity; carbon leakage; distributional effects; fiscal revenues